Moderate altitude has no effect on choice reaction time in international rugby players. Issue 2 (June 1997) - O'Carroll, R E; MacLeod, D
Abstract : There are only a few conflicting reports on the effects of moderate altitude on cognitive factors that could affect sporting performance. An investigation of choice reaction time in international rugby players at various altitudes was therefore carried out. The results suggest that moderate altitude has no significant effect on this parameter in highly trained competitive athletes.